ARDL Panel Prediction on the Management of Liquidity and Profitability of Islamic Banking in Muslim Emerging Market Countries: Evidence from Indonesia, Pakistan, Bangladesh, and Turkiye - Anwar Sanusi; Andri Soemitra; Isnaini Harahap (Journal of Economics and Management, 2026)
This study aims to analyze the prediction of Return on Assets (ROA) and Liquidity (LIK) in response to changes in macroeconomic indicators, namely Inflation, Money Supply, Exchange Rate, and Gross Domestic Product, with the expectation of maintaining their stability in Muslim emerging market countries: Indonesia, Pakistan, Bangladesh, and Turkiye. Data were analyzed using a Panel ARDL model for the period 2005 to 2023. ROA Prediction results indicate that Indonesia remains strong in controlling ROA through maintaining the stability of Inflation, Money Supply, Exchange Rate, Gross Domestic Product, and Liquidity. Pakistan, Bangladesh, and Turkiye similarly demonstrate strong ROA control through Inflation, Money Supply, Gross Domestic Product, and Liquidity, except for the Exchange Rate. Liquidity Prediction results indicate that Indonesia remains strong in controlling Liquidity through maintaining the stability of Inflation, Money Supply, Exchange Rate, Gross Domestic Product, and ROA. Pakistan, Bangladesh, and Turkiye demonstrate equally strong Liquidity control through Inflation, Money Supply, Gross Domestic Product, and ROA, except for the Exchange Rate. Policy implications suggest that monetary authorities must address the impact of monetary stability and eliminate obstacles to achieving ROA and Liquidity of Islamic banks by maintaining interaction, synergy, and harmonization between monetary policies and macroeconomic variables. The study acknowledges that interpretations must be made with care and encourages further exploration of Islamic bank liquidity and profitability from a macroeconomic perspective, as a stimulus for more comprehensive analysis, noting that monetary policy is considerably responsive in controlling macroeconomic stability.